Effects of the older student in digital formats: Digitalización del proceso de aprendizaje en un aula sénior - Lorente Guerrero, Xavier; Fernández Vidal, Mari Carmen (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
To carry out this work, an educational evaluation has been used from the CIPP model proposed by Stufflebeam and Shinkfield (1987). The sample is made up of 55 elderly people of Spanish nationality, aged between 55 and 82 years. The distribution in relation to gender groups 73% women and 27% men. Due to marital status, 36.3% are married, 45.4% are widowed, and 18.1% are single. The interpretation of pictograms in an EVEA is highlighted as an important visual and orientation element for correct handling by older students.